The Burden of Rheumatic Diseases: An Analysis of an Italian Administrative Database. Issue 1 (June 2016) - Iannazzo, Sergio; Furneri, Gianluca; Demma, Federica; Distante, Chiara; Parisi, Simone; Berti, Veronica; Fusaro, Enrico
Abstract Introduction Chronic inflammatory rheumatic diseases (RDs) trigger high costs for healthcare systems and society due to the disability and comorbidity associated with these disease entities. The aim of this study was to analyze patients with RD, assess the use of conventional synthetic and biologic therapies, and estimate the overall cost of treatment in Italy. Methods Administrative healthcare claims from the Piedmont region in Northwest Italy were reviewed to identify patients who received disease-modifying antirheumatic drugs (DMARDs) between 2007 and 2010. Confirmation of RD was based on: (1) diagnosis-specific exemption code; (2) hospitalization or emergency care events characterized by disease-specific ICD9 codes; (3) inclusion in the regional registry of biologic drugs. The follow-up period was 3 years. Results A total of 9560 subjects, of whom the majority were women (58.1%), were entered into the study; the average age of the study population was 55.3 years. On the index date 12.9% of patients were receiving a biologic DMARD, with adalimumab the most frequently prescribed biologic DMARD (4.7%), followed by etanercept (4.4%). The average total healthcare expenditure was €377.98 per patient per month (patient-month). In the subgroup analysis of healthcare costs according to use of biologics, the total expenditure was €1037.97/€230.86 patient-month for those receiving/not receiving at least one biologic DMARD. In the subgroup analysis of healthcare costs according to type of biologic used, the total expenditure ranged from €657.61 (golimumab) to €1384.15 (rituximab) patient-month. Conclusions A substantial difference in the total costs according to treatment/no treatment with a biologic and the specific biologic DMARD prescribed was identified. However, this result should be interpreted with caution as a bias in terms of patient selection was most likely present. The results of this study shed some light on RD in an relevant sample of Italian patients. The preliminary conclusions need to be confirmed by further analysis.